Three Drosophila beta-tubulin sequences: a developmentally regulated isoform (beta 3), the testis-specific isoform (beta 2), and an assembly-defective mutation of the testis-specific isoform (B2t8) reveal both an ancient divergence in metazoan isotypes and structural constraints for beta-tubulin function. - Rudolph, J E (1987)
The genomic DNA sequence and deduced amino acid sequence are presented for three Drosophila melanogaster beta-tubulins: a developmentally regulated isoform beta 3-tubulin, the wild-type testis-specific isoform beta 2-tubulin, and an ethyl methanesulfonate-induced assembly-defective mutation of the testis isoform, B2t8. The testis-specific beta 2-tubulin is highly homologous to the major vertebrate beta-tubulins, but beta 3-tubulin is considerably diverged. Comparison of the amino acid sequences of the two Drosophila isoforms to those of other beta-tubulins indicates that these two proteins are representative of an ancient sequence divergence event which at least preceded the split between lines leading to vertebrates and invertebrates. The intron/exon structures of the genes for beta 2- and beta 3-tubulin are not the same. The structure of the gene for the variant beta 3-tubulin isoform, but not that of the testis-specific beta 2-tubulin gene, is similar to that of vertebrate beta-tubulins. The mutation B2t8 in the gene for the testis-specific beta 2-tubulin defines a single amino acid residue required for normal assembly function of beta-tubulin. The sequence of the B2t8 gene is identical to that of the wild-type gene except for a single nucleotide change resulting in the substitution of lysine for glutamic acid at residue 288. This position falls at the junction between two major structural domains of the beta-tubulin molecule. Although this hinge region is relatively variable in sequence among different beta-tubulins, the residue corresponding to glu 288 of Drosophila beta 2-tubulin is highly conserved as an acidic amino acid not only in all other beta-tubulins but in alpha-tubulins as well.